Research and Application of Methodologies for Constructing Knowledge Graphs in Secondary School Mathematics - Wang, Hao; Xiong, Ke; Yu, Pengzhang (International Journal of Computer Science and Information Technology, 2024)
The knowledge graph of secondary school mathematics aims to enhance the efficiency and quality of mathematics teaching at the secondary level by constructing relationships between mathematical concepts. Traditional mathematics teaching often follows a linear approach, lacking flexibility and personalization. In contrast, methods based on knowledge graphs organize mathematical knowledge into graphical structures, enabling students to understand the connections and dependencies between various concepts more clearly. Utilizing Neo4j to store and manage the relationships between mathematical concepts provides comprehensive visual data support for the knowledge graph of mathematics. This approach may enhance students' interest and efficiency in learning mathematics and assist teachers in delivering better lessons.